Women, work and industrial relations in Australia in 2018. (June 2019) - Williamson, Sue; Foley, Meraiah; Cartwright, Natalie
This year's annual review of women, work and industrial relations marks an important milestone. Nearly 10 years have elapsed since the introduction of the Fair Work Act 2009, which enshrined important new rights for the progression of gender equality. It is also 10 years since the Journal of Industrial Relations commenced this annual review. In addition to focusing on developments affecting women and work in 2018, this review provides a broad summary of key events over the past decade. We explore trends in women's workforce participation, union membership, economic security and pay equity, as well as major changes pertaining to work–family policy settings, workplace sexual harassment, and family and domestic violence leave. We conclude that although policy and employment frameworks have created a foundation on which to build gender equality, policy development has been sporadic and the context for women in Australian workplaces remains far from equal.